Sept propositions pour soutenir et financer le secteur agricole en Afrique subsaharienne dans le contexte du changement climatique - Alain De Janvry; Elisabeth Sadoulet (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
– Poor rural households in vulnerable sub-Saharan Africa (SSA) countries have suffered - and will increasingly suffer - losses and damages due to climate change. These losses and damages put at risk the international commitment to meeting the Sustainable Development Goals. The international community is currently discussing a large scale increase in the financing of development assistance to meet this challenge. This note advances a set of propositions to guide international aid in addressing losses and damages due to climate change. The basic principle is that rather than focusing on targeted transfers to compensate for losses and damages - that will only increase over time and become prohibitively expensive -, the international community and SSA governments should seek to create income opportunities for affected rural households through a renewal of the role of agriculture for development, where under-investment relative to potential remains massive. We identify for this a sequence of steps that include Asset Building (land and human capital), Green Revolution (staple crops), Agricultural Transformation (high value crops and animal products), and Rural Transformation (rural-based Small and Medium Enterprises in agroindustry and agricultural services), ultimately converging to Structural Transformation (urban-based manufacturing and services). Successful implementation of this sequence is guided by seven propositions as to how to invest in agriculture for development in the context of climate change. Given the challenge of climate change, more than ever addressing the issue of risk reduction is a key component (on the demand side) of expected success in attracting private investment in agriculture. This can be achieved through irrigation, adoption of climate resilient crops and animals, index insurance, and parametric pre-committed lines of credit. We also review (on the supply side) results from experimental studies as to how to mobilize private funds for investment in agriculture through microfinance and commercial banks.
Keywords: 330